DIGITAL MARKETING TRAINING TO INCREASE MSME INCOME IN WATES HAMLET, TEJO VILLAGE, MOJOAGUNG, JOMBANG - Sudarti Sudarti; Rif’ati Dina Handayani; Aditya Kurniawan; Nurul Faridah (UNEJ e-Proceeding, 2022)
Nur Janah's shop is one of the micro businesses in Wates Hamlet that has felt the impact of Covid-19. Nur Janah's shop is quite large and complete, providing various kinds of household needs, but Nur Janah's shop does not have employees, this is because the daily income is not clear and is not enough to pay employees. Merchandise is piling up, there is no marketing effort and not familiar with online sales because of a lack of knowledge of technology. In addition, this shop is also located quite hidden in the hamlet, with the target market only local villagers. This activity aims to provide digital marketing training for the family of the owner of the Nur Janah Store. The training method is carried out through direct private training for 6 times every Saturday. The results of the activity show that Mrs. Nur Janah and her 2 children are already skilled in digital marketing. The impact of this activity is that there is an optimization on the Tokopedia MSME account of the Nur Janah store in terms of product design and description Keywords: Digital marketing, MSME, Marketplace